Recent Advances in Membrane Shaping for Plant Autophagosome Biogenesis - Wun, Cheuk-Ling; Quan, Yingfei; Zhuang, Xiaohong (Frontiers in Plant Science, 2020)
Autophagy is an intracellular degradation process, which is highly conserved in eukaryotes. During this process, unwanted cytosolic constituents are sequestered and delivered into the vacuole/lysosome by a double-membrane organelle known as an autophagosome. The autophagosome usually initiates from a membrane sac named the phagophore, and after phagophore expansion and closure, the outer membrane fuses with the vacuole/lysosome to release the autophagic body into the vacuole. Therefore, it requires de novo membrane sources and distinct membrane remodelling machineries to function in different stages. In this review, we will update recent findings with a focus on comparing the core tethering complexes involved in shaping the autophagosome membrane in yeast, mammal and plant systems.